The Influence of Intellectual Capital on Corporate Financial Performance - Dimas Novianto Kurniawan; Supriyadi Supriyadi; Rhoma Iskandar (Applied AI and Machine Learning Journal, 2026)
Purpose: This study aims to examine and obtain empirical evidence on the effect of intellectual capital on the financial performance of food and beverage manufacturing companies listed on the Indonesia Stock Exchange (Bursa Efek Indonesia/BEI) during 2020–2024. Research Methodology: A quantitative approach was used with secondary data from annual financial reports. Intellectual capital was measured using the Value-Added Intellectual Coefficient (VAIC™), while financial performance was assessed through Return on Assets (ROA). The sample consisted of 12 companies, with 60 firm-year observations, analyzed using descriptive statistics, Pearson’s correlation, and simple linear regression with SPSS. Results: The study found that intellectual capital has a negative and statistically insignificant effect on financial performance (? = ?4.144E?05, t = ?0.232, p = 0.817), with an R² of 0.001, indicating that intellectual capital explains only 0.1% of the variation in ROA. The Pearson correlation between VAIC™ and ROA was ?0.030 (p = 0.409).. Conclusions: The findings suggest that intellectual capital does not significantly influence financial performance in the food and beverage sector. Other factors may explain the majority of the variation in ROA. The study contributes to the accounting literature by providing empirical evidence on intellectual capital’s role in financial performance in post-pandemic Indonesia. Limitations: The study is limited by its sample size and sector focus, and the VAIC™ method may not fully capture the true value of human capital. Contributions: This research adds to the understanding of intellectual capital’s influence on financial performance in the Indonesian food and beverage industry.